PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KECAP MEREK ANGSA PADA PT KILANG KECAP ANGSA - Christian Sitompul, Sintong Lewis (EDUTECH CONSULTANT, 2019)
The research objective was to test and analyze the effect of product quality and brand image on the purchase decision of the Angsa brand soy sauce at the PT Soy Sauce Refinery. This study uses a quantitative research approach. Type of quantitative descriptive research. The population of 150 respondents from the Kappa Kecsa Anggran which was used as a sample of 110 respondents of this study and 30 people of PT Kilang Kecap Angsa which were tested outside the study sample validity and reliability. Analysis of multiple linear regression data and testing of classical assumptions, namely normality, multicollinearity and heterocedasticity. The results of the study which were the conclusions were that the product quality had a significant and significant effect on the purchase decision of the Angsa brand soy sauce at the PT Soy Sauce Refinery. Brand image influences and significantly influences the purchase decision of the Angsa brand soy sauce at the PT Soy Sauce Refinery. Product quality and brand image have a positive and significant effect on the purchase decision of the Angsa brand soy sauce at the PT Soy Sauce Refinery.